Uncertain effectiveness of Miscanthus bioenergy expansion for climate change mitigation explored using land surface, agronomic and integrated assessment models. Issue 3 (4th January 2023) - Littleton, Emma W.; Shepherd, Anita; Harper, Anna B.; Hastings, Astley F. S.; Vaughan, Naomi E.; Doelman, Jonathan; van Vuuren, Detlef P.; Lenton, Timothy M.
Abstract: Large‐scale bioenergy plays a key role in climate change mitigation scenarios, but its efficacy is uncertain. This study aims to quantify that uncertainty by contrasting the results of three different types of models under the same mitigation scenario (RCP2.6‐SSP2), consistent with a 2°C temperature target. This analysis focuses on a single bioenergy feedstock, Miscanthus  ×  giganteus, and contrasts projections for its yields and environmental effects from an integrated assessment model (IMAGE), a land surface and dynamic global vegetation model tailored to Miscanthus bioenergy (JULES) and a bioenergy crop model (MiscanFor). Under the present climate, JULES, IMAGE and MiscanFor capture the observed magnitude and variability in Miscanthus yields across Europe; yet in the tropics JULES and IMAGE predict high yields, whereas MiscanFor predicts widespread drought‐related diebacks. 2040–2049 projections show there is a rapid scale up of over 200 Mha bioenergy cropping area in the tropics. Resulting biomass yield ranges from 12 (MiscanFor) to 39 (JULES) Gt dry matter over that decade. Change in soil carbon ranges from +0.7 Pg C (MiscanFor) to −2.8 Pg C (JULES), depending on preceding land cover and soil carbon.2090–99 projections show large‐scale biomass energy with carbon capture and storage (BECCS) is projected in Europe. The models agree that <2°C global warming will increase yields in the higher latitudes, but drought stress in the Mediterranean region could produce low yields (MiscanFor), and significant losses of soil carbon (JULES and IMAGE). These results highlight the uncertainty in rapidly scaling‐up biomass energy supply, especially in dry tropical climates and in regions where future climate change could result in drier conditions. This has important policy implications—because prominently used scenarios to limit warming to 'well below 2°C' (including the one explored here) depend upon its effectiveness. Abstract : This study compares yields and soil carbon impacts of meeting future bioenergy demand with large‐scale plantation of Miscanthus, using three different types of global model. The dedicated crop model (MiscanFor) shows high yields in Europe but poor performance in the tropics, with an increase in soil carbon with cultivation. The land surface model (JULES) and the integrated assessment model (IMAGE) show higher yields in the tropics but greater losses of soil carbon due to land use change. These results highlight the uncertainty in rapidly increasing the supply of biomass energy.